The efficacy of virtual reality exposure therapy for the treatment of alcohol use disorder among adult males: a randomized controlled trial comparing with acceptance and commitment therapy and treatment as usual - Deng, Hongdu; Zhang, Ruiling; Wang, Chuansheng; Zhang, Bingyu; Wang, Jiali; Wang, Shilin; Zhang, Jie; Shari, Nurul Izzah; Leong Bin Abdullah, Mohammad Farris Iman (Frontiers in Psychiatry, 2023)
Background This multicenter, three-armed, parallel, single-blind randomized controlled trial (RCT) primarily aims to compare the efficacy of virtual reality exposure therapy (VRET) with that of acceptance and commitment therapy (ACT) and treatment as usual (TAU) to depreciate the degree of alcohol craving among alcohol use disorder patients who have undergone in-patient detoxification across four timelines (t0 = baseline prior to intervention, t1 = 4 weeks after baseline, t2 = 12 weeks after baseline, and t3 = 24 weeks after baseline). The secondary aims of this RCT are to compare the efficacy of VRET with that of ACT and TAU to alleviate the severity of alcohol use disorder, dissipate comorbid depressive and anxiety symptoms, and normalize event-related potential (ERP) in electroencephalogram (EEG) monitoring across the four timelines. Methods Initially, after 2 weeks of in-patient detoxification, 120 patients with alcohol use disorder will be randomized into three groups (VRET, ACT, and TAU control groups) via stratified permuted block randomization in a 1:1:1 ratio. Baseline assessment (t0) commences, whereby all the participants will be administered with sociodemographic, clinical, and alcohol use characteristics questionnaire, such as Alcohol Use Disorder Identification Test (AUDIT), Penn Alcohol Craving Scale (PACS), Hamilton Anxiety Rating Scale (HAM-A), and Hamilton Depression Rating Scale (HAM-D), while event-related potential (ERP) detection in electroencephalogram (EEG) will also be carried out. Then, 4 weeks of VRET, ACT, and non-therapeutic supportive activities will be conducted in the three respective groups. For the subsequent three assessment timelines (t1, t2, and t3), the alcohol use characteristic questionnaire, such as AUDIT, PACS, HAM-D, HAM-A, and ERP monitoring, will be re-administered to all participants. Discussion As data on the effects of non-pharmacological interventions, such as VRET and ACT, on the treatment of alcohol craving and preventing relapse in alcohol use disorder are lacking, this RCT fills the research gap by providing these important data to treating clinicians. If proven efficacious, the efficacy of VRET and ACT for the treatment of other substance use disorders should also be investigated in future. Clinical trial registration NCT05841823 (ClinicalTrials.gov).